2019
DOI: 10.3390/met10010050
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Electrodeposition of Gold Process in Iodine Leaching Solution

Abstract: This paper mainly discusses electrodeposition of gold from iodine leaching solution through single-factor testing and explores the influence of gold concentration in catholyte, mass fraction of iodine in anolyte, anolyte n(I2):n(I−), cell voltage, and electrolysis time on the percentage of gold deposition and coulombic efficiency. Moreover, a response surface methodology was adopted to study interactions among variables and influence on the percentage of gold deposition, with mass fraction of iodine in anolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Au Recovery. Based on the findings of previous authors [1], [12] , it can be expected that the application of the 12.9 V cell voltage during the laboratory experiment resulted in the transport of dissolved Au-iodide ions (primarily as AuI2 − ) from the WPCB iodide leachate in the feed tank to the surface of the cathode in the catholyte tank where they underwent a reduction reaction (equation 2) which produced iodide ions and the solid Au deposit which was observed on the cathode surface as a brown powder. While iodide ions in the catholyte tank are believed to be transported (through the AEM) to the surface of the anode in the anolyte tank where they were oxidized to di-iodine (equation 3).…”
Section: Results In Tablementioning
confidence: 96%
See 1 more Smart Citation
“…Au Recovery. Based on the findings of previous authors [1], [12] , it can be expected that the application of the 12.9 V cell voltage during the laboratory experiment resulted in the transport of dissolved Au-iodide ions (primarily as AuI2 − ) from the WPCB iodide leachate in the feed tank to the surface of the cathode in the catholyte tank where they underwent a reduction reaction (equation 2) which produced iodide ions and the solid Au deposit which was observed on the cathode surface as a brown powder. While iodide ions in the catholyte tank are believed to be transported (through the AEM) to the surface of the anode in the anolyte tank where they were oxidized to di-iodine (equation 3).…”
Section: Results In Tablementioning
confidence: 96%
“…Although iodide lixiviants have been reported to be highly effective at leaching Au from WPCBs, there remains an issue on how to recover Au from WPCB iodide leachates in an efficient and economically feasible manner. [12], [11] Previous authors have reported the high yield (> 99 %) recovery of Au from WPCB iodide leachates by reductive precipitation under highly acidic (pH < 1.6) and alkaline conditions (pH > 13) induced by 0.1 M ascorbic acid and 0.1 M sodium hydroxide respectively. [11] However, considering the complex metal compositions of WPCB iodide leachates, extensive co-precipitation of impurities is expected to occur, resulting in the need for further beneficiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, electrodeposition of gold from iodine leaching solution using response surface methodology was used to study the interactions between variables and their effect on gold deposition rate. The proposed method showed a high deposition rate (94.02%), but a low coulombic efficiency (2.53%) [41].…”
Section: Brominementioning
confidence: 94%
“…While electrocatalysis can be carried out in a variety of media, non-aqueous eutectic mixtures can decrease passivation of some metals, while careful selection of the redox catalyst can enable selective solubilisation of metals from complex mixtures 37,55 . For instance, iodine has been reported as a strong oxidising agent for metal and mineral digestion, particularly for solubilising gold in a wide variety of solvents, both aqueous and non-aqueous systems 52,53,[55][56][57][58][59][60][61][62] . Iron(III) chloride (FeCl 3 ) and copper(II) chloride (CuCl 2 ) have also been reported as redox catalysts in different ionic uids and brines, for the dissolution of metals from solar photovoltaic cells and printed circuit boards.…”
Section: Redox Catalysts In Dess -A Brief Summarymentioning
confidence: 99%